A NOTE ON THE FOOD OF MYSTUS VITTATUS (BLOCK) FROM THE HIGHLY POLLUTED HUSSAIN SAGAR LAKE, HYDERABAD - Reddy, Y Siva; Rao, Babu (Indian Journal of Fisheries, 2011)
Mystus vittatus (Bloch) in the highly polluted Hussain Sagar feed mainly on insect larvae and insects. The other food items include both plant and animal matter. Intensive feeding is during December to February.